Magnetophoresis Induced Hydrodynamic Flow Of Non-Newtonian Fluid - Ong, Yi Qian (Universiti Sains Malaysia, 2018)
For heterogeneous mixture, there are some separation techniques can be used to separate the mixture into individual component. For example, centrifugation, filtration and also adsorption. Adsorption is the most efficient and cost effective methods compared to other separation techniques. Magnetic separation by using magnetic nanoparticles is one of the adsorption methods and is gaining more popularity among other techniques. However, when the size of the materials involved are reduced to nano size, the particles behavior in terms of flow, mixing and other phenomena will be different with macroscopic materials. This makes the reason to analyze and investigate the nanoparticles behavior and the interaction involved when the nanoparticles are inside the fluid medium. Low gradient magnetic separation is used to investigate the hydrodynamic flow of the particles when the aggregation parameter is fixed at below unity. The main focus in this research is the hydrodynamic effect in non-Newtonian. The magnetic Grashof number calculated for MNPs solution in Newtonian fluid is greater than in non-Newtonian fluid. This indicates that the magnetic buoyancy and also the fluid convection in Newtonian fluid significant is more significant than that in non- Newtonian fluid.